Dosing Time Matters? Nighttime vs. Daytime Administration of Nifedipine Gastrointestinal Therapeutic System (GITS) or Amlodipine on Non-dipper Hypertension: A Randomized Controlled Trial of NARRAS - Liu, Jing; Su, Xiaofeng; Nie, Ying; Zeng, Zhihuan; Chen, Hongyan (Frontiers in Cardiovascular Medicine, 2021)
Background: Non-dipper hypertension is often characterized by a blunted decrease of nocturnal blood pressure (BP) and is associated with increased risk of target organ damage and cardiovascular (CV) events, while the optimal treatment strategy is yet to be established. This trial was designed to evaluate whether nocturnal BP reduction and arterial stiffness improvement differ from antihypertensive agents and time of administration. Methods: Young and middle-aged adults (18–65 years) with non-dipper hypertension were randomly assigned to nifedipine GITS (gastrointestinal therapeutic system) 30 mg or amlodipine besylate 5 mg once daily for 8 weeks, either taken in the morning or at night. Dose was doubled at 4-week if BP is not at goal. Twenty-four hour ambulatory BP monitoring (ABPM) and arterial stiffness were evaluated before and after 8 weeks of pharmacotherapy. The primary efficacy measure was the average nighttime systolic BP reduction. Results: A total of 98 non-dipper hypertensive patients (mean age 46.3 years) were randomized during Dec, 2016 and Dec, 2020, of whom 72 (73%) patients completed all ABPM and follow-up evaluations. Nighttime systolic BP significantly reduced at 8 weeks vs. baseline with nifedipine GITS or amlodipine, irrespective of dosing at nighttime (−9.9 vs −9.9 mmHg, P > 0.05) or daytime (−11.5 vs. −10.9 mmHg, P > 0.05). No difference was seen between these two agents, when combining the data of nighttime and daytime dosing together (−10.8 vs. −10.5 mmHg, respectively, P = 0.898). Daytime, 24-h systolic BP, diastolic BP at different time and pulse wave velocity reduced significantly and comparably, and recovery of dipping rhythm were similar among groups. Conclusion: Nighttime dosing of long-acting antihypertensive preparations, nifedipine GITS or amlodipine demonstrated similar effects on nocturnal BP reduction, dipping rhythm restoration and arterial elasticity improvement in younger subjects with non-dipper hypertension. These effects were comparable with morning dosing.